Administrative Service Standards Based on Local Wisdom : JEL Classification: H83, H11, Z18, D73, R58 - Sakbir Sakbir (Newinera Publisher, 2026)
This study aims to describe the Local Wisdom-Based Administrative Service Standards at the Buntulia District Office, Pohuwato Regency. The research method uses a qualitative approach with data collection through observation, interviews and documentation. The results of the study indicate that the implementation of Local Wisdom-Based Administrative Service Standards at the Buntulia District Office, Pohuwato Regency is not optimal. This can be seen from the unclear service flow and prioritizes subjectivity, where someone who has influence can get services without going through the proper procedures. Furthermore, no documents or written rules were found that show the rules related to the service time required for each type of service, in fact there were exceptions for certain people to get much faster services than ordinary people who have to wait according to the arrival queue. Likewise, in terms of service costs, there are no rules or standards that regulate it so that there is the potential for illegal levies from irresponsible individuals even though basically related to service costs have been regulated in the Pohuwato Regent Regulation Number 6 of 2022 concerning Integrated Population Administration Management Without Fees and Population Administration Management for Zoning Villages